To What Extent Does the Food Industry Disclosing Carbon Emissions GRI 305-Based Analysis in the Indonesian Capital Market - Rais, Anisatun Humayrah; Said, Siti Nur Reskiyawati (Phinisi Applied Accounting Journal, 2025)
This study analyzes the extent of carbon emission disclosure among food and beverage companies listed on the Indonesia Stock Exchange using the GRI 305 framework. Although climate-related reporting is increasingly important, prior studies show that emission disclosures in Indonesia remain voluntary and uneven. This research fills that gap by evaluating six core GRI 305 indicators through content analysis of sustainability and annual reports for 2021–2024. The results show a moderate disclosure level, with an average score of 4.45 out of 7 (index 0.64). Companies most frequently report Scope 1, Scope 2, and emission intensity, while Scope 3 is rarely disclosed. Disclosure declined slightly in 202–2023 but improved in 2024. These patterns indicate selective reporting focused on indicators under direct managerial control. The findings provide input for regulators and stakeholders to strengthen climate-related transparency in Indonesia.Studi ini menganalisis tingkat pengungkapan emisi karbon di antara perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia menggunakan kerangka kerja GRI 305. Meskipun pelaporan terkait iklim semakin penting, studi sebelumnya menunjukkan bahwa pengungkapan emisi di Indonesia masih bersifat sukarela dan tidak merata. Penelitian ini mengisi kesenjangan tersebut dengan mengevaluasi enam indikator inti GRI 305 melalui analisis isi laporan keberlanjutan dan tahunan untuk periode 2021–2024. Hasilnya menunjukkan tingkat pengungkapan yang moderat, dengan skor rata-rata 4,45 dari 7 (indeks 0,64). Perusahaan paling sering melaporkan Cakupan 1, Cakupan 2, dan intensitas emisi, sementara Cakupan 3 jarang diungkapkan. Pengungkapan sedikit menurun pada periode 202–2023 tetapi membaik pada tahun 2024. Pola-pola ini menunjukkan pelaporan selektif yang berfokus pada indikator-indikator di bawah kendali langsung manajerial. Temuan ini memberikan masukan bagi regulator dan pemangku kepentingan untuk memperkuat transparansi terkait iklim di Indonesia.